Three Dimensional Extension for Park and Ang Damage Model. (August 2016) - Guo, J.; Wang, J.J.; Li, Y.; Zhao, W.G.; Du, Y.L.
Abstract: The proper evaluation of the damage of a structural member lays the basis for the performance-based seismic design procedure. The damage in a reinforced concrete (RC) pier due to an earthquake may be three dimensional, i.e., biaxial bending with a varying axial load. However, the existing damage models generally can be applied only to one dimensional cases, i.e., uniaxial bending with a constant axial load. To compensate for this gap, the conventional widely-used Park and Ang damage model is extended to account for cases of three dimensional damage in this paper. The newly developed model is based on the moment-rotation relationship. The determination of relevant variables in the proposed model is presented in detail. Two unknown parameters are determined from experimental data through two rounds of traversal search. In addition, a new set of performance levels compatible with this extended Park and Ang model is defined. The applicability of the damage model under various one-dimensional loading paths and under spatial loadings is verified. The results indicate that the extended Park and Ang damage model, together with the parameters and the performance leveling criterion, constitutes an integrated damage assessment index, that can effectively evaluate the three dimensional damage of an RC pier.